Analisis Penerapan Workplace Spirituality dalam Meningkatkan Produktivitas Karyawan pada BTN KCS Padang - Pratiwi, Nia; Alfin, Aidil (ARZUSIN, 2026)
Workplace spirituality has received attention in various studies because it is considered capable of creating a more harmonious, meaningful, and productive work environment. However, research specifically examining the application of workplace spirituality in increasing employee productivity in Islamic financial institutions remains limited, particularly at Bank Tabungan Negara Sharia Branch Office (BTN KCS) Padang. This study aims to analyze the application of workplace spirituality in increasing employee productivity at BTN KCS Padang. This study used a qualitative approach with a descriptive case study design, involving 23 employees as participants selected through purposive sampling. Data were collected through semi-structured interviews, observation, and documentation, and were then analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The results showed that workplace spirituality was applied through various spiritual activities and Islamic work culture, such as reading the Qur’an together, collective prayer, regular religious study sessions, Friday short sermons, congregational prayers, and the habituation of greeting and smiling in service to customers. The application of workplace spirituality had a positive impact on improving work focus, motivation, discipline, social relationships among employees, and service quality for customers. The conclusion of this study affirms that workplace spirituality plays an important role in building a religious, harmonious, and productive work culture in Islamic financial institutions. These findings contribute to the development of workplace spirituality studies in the context of Islamic banking and provide practical implications for strengthening Islamic work culture to increase employee productivity.